2020
DOI: 10.1016/j.oneear.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The Greening of the Sahara: Past Changes and Future Implications

Abstract: In the future, the Sahara and Sahelian regions could experience more rainfall than today as a result of climate change. Wetter periods, termed African humid periods, occurred in the past and witnessed a mesic landscape in place of today's hyperarid and semiarid environment. Such large past changes raise the question of whether the near future might hold in store similar environmental transformations, particularly in view of the growing human-induced climate, land-use, and land-cover changes. In the last decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
123
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(132 citation statements)
references
References 191 publications
6
123
0
3
Order By: Relevance
“…Another confounding factor that may have contributed to changes in local precipitation within the tropics is the expansion of the tropical rainforests in the PlioMIP simulations. For instance, a northward expansion of the tropical vegetation in Africa is known to increase precipitation in the Northern Hemisphere tropics, decrease trade winds and, thus warm the tropical North Atlantic 48 . It is important to note that the PlioMIP initiative focuses on a single interglacial time slice (KM5c at ~ 3.2 Ma) within the mid-Pliocene Warm Period 4 (3–3.3 Ma).…”
Section: Discussionmentioning
confidence: 99%
“…Another confounding factor that may have contributed to changes in local precipitation within the tropics is the expansion of the tropical rainforests in the PlioMIP simulations. For instance, a northward expansion of the tropical vegetation in Africa is known to increase precipitation in the Northern Hemisphere tropics, decrease trade winds and, thus warm the tropical North Atlantic 48 . It is important to note that the PlioMIP initiative focuses on a single interglacial time slice (KM5c at ~ 3.2 Ma) within the mid-Pliocene Warm Period 4 (3–3.3 Ma).…”
Section: Discussionmentioning
confidence: 99%
“…The mid- to late Holocene, roughly 6 to 4 thousand years ago (ka), was characterized by one of the largest climate shifts since the last glacial termination—the end of the Green Sahara (also referred to as the African Humid Period), when a once-vegetated northern Africa transitioned to a hyper-arid desert landscape 2 5 . 'Both the nature and timing of this climate shift have been topics of great interest because it overlaps with societal upheavals across western Asia and the Middle East.…”
Section: Introductionmentioning
confidence: 99%
“…The important role of feedbacks in maintaining a fundamentally different climate state provides another incentive for studying the mid-Holocene, because understanding them can also help us better appreciate the changes in the northern parts of Africa to be expected from ongoing climate change and regional human activity (Pausata et al, 2020). For instance, Charney (1975) and Charney et al (1975) have shown that the increase in albedo arising from decrease in vegetation can induce persistent regional atmospheric subsidence leading to reduced precipitation and further reduction in vegetation, creating a positive feedback that supports persistent desertification.…”
Section: Introductionmentioning
confidence: 99%